2015
DOI: 10.1039/c5ra04102c
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented formation of spiro[indoline-3,7′-pyrrolo[1,2-a]azepine] from multicomponent reaction of l-proline, isatin and but-2-ynedioate

Abstract: Spiro[indoline-3,3′-pyrrolizines] and spiro[indoline-3,7′-pyrrolo[1,2-a]azepines] can be selectively produced from three-component reaction of α-amino acids, isatins and but-2-ynedioates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…The asymmetric skeleton of spirans is an important criterion for their biological activities. [1][2][3][4][5] Huisgen intermediates, generated from aromatic N-heterocycles (pyridine, isoquinoline, quinoline, etc) and electron-deficient acetylenic esters, [6][7][8][9] are important in the synthesis of heterocyclic spirans.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The asymmetric skeleton of spirans is an important criterion for their biological activities. [1][2][3][4][5] Huisgen intermediates, generated from aromatic N-heterocycles (pyridine, isoquinoline, quinoline, etc) and electron-deficient acetylenic esters, [6][7][8][9] are important in the synthesis of heterocyclic spirans.…”
Section: Introductionmentioning
confidence: 99%
“…Spirocyclic structures (spirans) fused at a central carbon atom are a privileged class of natural substances that exhibit biological properties, and hence, their synthesis has been an attraction to organic chemists. The asymmetric skeleton of spirans is an important criterion for their biological activities . Huisgen intermediates, generated from aromatic N‐heterocycles (pyridine, isoquinoline, quinoline, etc) and electron‐deficient acetylenic esters, are important in the synthesis of heterocyclic spirans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[44] In recent years, we have deeply investigated 1,3-dipolar cycloaddition reactions of heterocyclic nitrogen N-ylides with 3-methyleneoxindole derivatives and found that versatile spirooxindole systems can be selectively synthesized by changing of the substrates and reaction conditions. [45][46][47][48][49][50][51][52][53][54][55] In order to further explore versatile reactivity of heterocyclic nitrogen N-ylides in 1,3-dipolar cycloadditions and provide more efficient synthetic methodology for spirocyclic compounds, …”
Section: Introductionmentioning
confidence: 99%
“…Due to the spirooxindole existing in a large number of naturally occurring and medicinally relevant substances, the development of efficient method for constructing the spirooxindole motif is of great importance in synthetic organic and medicinal chemistry6566676869707172. Against this background and in continuation of our efforts to develop new efficient synthetic methods for complex spirooxindoles7374757677787980818283, herein we wish to report the interesting results of three-component reactions of N -(4-nitrobenzyl), N -ethoxycarbonylmethyl and N -cyanomethylisoquinolinium salts with isatins and malononitrile as well as ethyl cyanoacetate.…”
mentioning
confidence: 99%